Health promotion for Latin Americans with intellectual disabilities Promoción de la salud para latinoamericanos con discapacidad intelectual - Georgia C Frey; Viviene A Temple (Instituto Nacional de Salud Pública, 2008)
In response to the emerging global concern regarding health and people with intellectual disabilities (ID), several developed countries have established national initiatives to address the unique health needs of this population segment. However, most people with ID reside in countries with developing economies, such as many Latin American countries, yet there is virtually no information on the health of people with ID in these regions. Countries with developing economies face distinct challenges in promoting health among this population segment that may preclude adoption or adaptation of policies and practices developed in regions with established economies. This paper will address the issue of health promotion among people with ID in Latin America, an area that is undergoing significant reforms in both health care and disability rights. Information on the social and health status of Latin Americans with ID, as well as research on health promotion best practices, will be used to develop recommendations for promoting health for these individuals. En respuesta al interés que están despertando en el mundo la salud y la persona de quienes padecen discapacidad intelectual (DI), varios países desarrollados han establecido iniciativas nacionales para atender las necesidades de salud particulares de este segmento de la población. Sin embargo, la mayoría de las personas con DI residen en países con economías en vías de desarrollo, como muchos países latinoamericanos, donde la información acerca de ellas es escasa. Los países con economías en vías de desarrollo enfrentan sus propios retos para promover la salud en este segmento de la población, los cuales pueden impedir o dificultar la adopción o la adaptación de las políticas y prácticas establecidas en países con economías desarrolladas. Este artículo está dedicado a la promoción de la salud de la gente con DI en Latinoamérica, región donde se están llevando a cabo importantes cambios tanto en la atención a la salud como en los derechos de la discapacidad. Para desarrollar recomendaciones para promover la salud de las personas con DI, se utilizará información sobre el estado social y de salud de los latinoamericanos con DI y sobre la investigación de las mejores prácticas de promoción de la salud.